Feminismo islâmico : um movimento político-religioso transnacional - Costa, Mariana de Medeiros (2021)
The present work has as object of study the Islamic feminism, a transnational political-religious movement that is based on the re-reading of the sacred scriptures for Islam. Islamic feminists defend the idea that patriarchy is not inherent in Islam and that an emancipatory reading of the Qur’an is possible. Thus, they put the discussion of gender in Islam on the agenda and question the Islamic legal tradition. The objective here is to map the productions on Islamic feminism in order to demonstrate the need to open space for non-Western feminist approaches that can contribute to the production of knowledge in International Relations.